A comparative analysis of the written English used in 1969 and 1970 by English I students who participated in the English language tutional scheme at the University of Cape Town - Fielding, Michael Lonsdale (Department of English Language and Literature, 2015)
This examination of students' writing, based on essays written by selected groups of students who participated in the English Language Tutorial Scheme in l969 and 1970, is aimed at establishing what the stylistic, lexical, grammatical and syntactical difficulties of students are. In this way, the approach of tutors may be confirmed or adapted, so that the general weaknesses of students can be concentrated on and the satisfactory aspects of their written composition can be ignored. In this way valuable time need not be wasted on unnecessary teaching.